2021
DOI: 10.2147/opth.s318026
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Management of Center-Involving Diabetic Macular Edema: Treatment Options and Patient Monitorization

Abstract: Diabetic macular edema (DME) is the main cause of visual impairment associated with diabetic retinopathy (DR) and macular laser, during approximately three decades, and was the single treatment option. More recently, intravitreous injections of anti-angiogenics and corticosteroids modified the treatment paradigm associated with significant vision improvements. Nevertheless, not all patients respond satisfactorily to anti-VEGF or corticosteroid injections, so an adequate treatment choice and a prompt switch in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…Several anti-VEGF treatment regimens have been developed, such as monthly or bimonthly injections, pro re nata (PRN), and treat and extend (TAE) regimen [ 16 ]. PRN is the most common regimen in the treatment for DME to optimize the treatment effects and cost-effectiveness [ 17 ]. Many random clinical trials recommend three loading doses of anti-VEGF injections followed by a PRN regimen, namely, 3 + PRN [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several anti-VEGF treatment regimens have been developed, such as monthly or bimonthly injections, pro re nata (PRN), and treat and extend (TAE) regimen [ 16 ]. PRN is the most common regimen in the treatment for DME to optimize the treatment effects and cost-effectiveness [ 17 ]. Many random clinical trials recommend three loading doses of anti-VEGF injections followed by a PRN regimen, namely, 3 + PRN [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…PRN is the most common regimen in the treatment for DME to optimize the treatment effects and cost-effectiveness [ 17 ]. Many random clinical trials recommend three loading doses of anti-VEGF injections followed by a PRN regimen, namely, 3 + PRN [ 17 ]. But in the real world, three loading injections would be a great economic and psychological burden for patients with DME, especially in developing countries [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggested that vision has significantly improved before and after intravitreal injection of conbercept in the CI-DME group. Some clinical trials have demonstrated that anti-VEGF therapy has been adopted as the first-line therapy in CI-DME ( 5 7 , 27 ) and it is more effective in improving the vision and visual acuity in CI-DME compared with focal laser treatment. Anti-VEGF treatment blocked the formation of neovascularization and reduced retinal thickening ( 5 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…All of them are naive patients who have never been diagnosed and treated. Informed consent was obtained from all patients who received intravitreal conbercept injection ( 5 7 , 25 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation